Geomorphic rehabilitation, landscape evolution and hydraulic modelling for the closure of Cerrejón mine, Colombia - Martín Duque, J.F.; Hancock, G.R.; Tejedor, M.; Bladé, E.; Sánchez, R.; Gómez, Á.; Fuentes, C.A.; Madriñan, L.F.; Lozano, J.P.; Castro, E. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
This paper describes the first use of geomorphic landform design (GLD) and landscape evolution modelling (LEM) for mine rehabilitation and closure in a South American context. These methods are being applied at the largest open pit mine on this continent and one of the largest worldwide: Cerrejón (Colombia). GLD (using GeoFluv-Natural Regrade software) is being introduced here at several large waste rock dumps (WRD) without jeopardising volume storage or footprint requirements, with clear advantages in terms of predicted water erosion stability – aiming to avoid ‘spillage’ erosion processes from platforms and berms – and ecological, hydrological and visual integration with the surroundings. However, some challenges are yet to be solved, such as minimising earth movements for the reshaping of existing WRD and a fluent integration between geomorphic designs and mine planning. The SIBERIA modelling always forecasts less erosion rates for the geomorphic alternatives than for the conventional topographies, with very significant differences at one site (La Estrella WRD) and with one order of magnitude of difference: 66.1 t ha-1 yr-1 predicted for conventional topography and 6.9 t ha-1 yr-1 for geomorphic, for year 300. The geomorphic designs are prone to some localised gullying in the main drainage lines, but this maximum erosion (gully) depth is around one third less than for the conventional alternative. This modelling is preliminary and provisional until proper calibration for the site will be available. However, with the same parameters for both modelling sets, the tendencies are clearly in favour of the geomorphic alternative. In order to better understand this gullying process at the drainage lines, and to avoid it, the GLD for the Cerrejón mine is being subjected to hydrologic and hydraulic modelling with Iber, a 2D hydraulic model for the simulation of free surface flow in rivers. This allowed us to obtain water depths and velocities, bed shear stresses and critical diameters for each drainage line of the GLD. With this information, armouring or hydraulic works are being designed.